A comprehensive review on hydrogen production from coal gasification: Challenges and Opportunities. (21st July 2021) - Midilli, Adnan; Kucuk, Haydar; Topal, Muhammed Emin; Akbulut, Ugur; Dincer, Ibrahim
Abstract: This paper comparatively discusses hydrogen production options through coal gasification, including plasma methods, and evaluate them for practical applications. In this regard, it focuses on numerous aspects of hydrogen production from coal gasification, including (i) state of the art and comparative evaluation, (ii) environmental and economic dimensions, (iii) energetic and exergetic aspects, (iv) challenges, opportunities and future directions. Furthermore, this review paper outlines what differences it brings in and what contributions it makes to the current literature about such a significant domain of potential hydrogen production which can be used as clean fuel, energy carrier and feedstock. Accordingly, this comprehensive review offers some results as follows: (i) plasma gasification system produces higher amount of hydrogen from other gasification processes, (ii) less amounts of solid wastes (slag, ash, tar, etc.) are released during plasma gasification process compared to other gasification processes, and (iii) it is overall more sustainable Thus, plasma gasification is proposed as a potential option for hydrogen fuel production from coals and for practical application in energy sector. As a case study, some plasma gasifiers in the literature are analyzed in terms of the exergetic sustainability. Furthermore, the case study results show that the exergetic sustainability index decreases from 0.642 to 0.186, and the exergetic efficiency drops from 0.342 to 0.156, while the environmental impact factor increases from 1.556 to 5.372 with an increase of waste exergy ratio from 0.839 to 0.532, respectively. Highlights: Hydrogen production from coal is efficiently conducted by applying gasification techniques. Energetic, economic, environmental and sustainability aspects are important for better evaluating the gasification methods. For a higher amount of hydrogen production from low quality coal, plasma gasification technique can be a more efficient and effective solution. Plasma gasification process results in less wastes compared to other gasification processes. Plasma gasification is more environmentally friendly, more efficient and hence more sustainable than other gasification methods.